The Role of Cost Accounting in the Efficiency of Healthcare Services - Sarah Michelle; An.Nisa Rahma Sari; Dwi Noerjoedianto; Adila Solida (CV. AFDIFAL MAJU BERKAH, 2026)
The efficiency of healthcare services is a major challenge in managing healthcare facilities, particularly due to increasing demands for service quality and limited available resources. Ineffective cost management can reduce the performance of healthcare organizations and disrupt service sustainability; therefore, cost accounting is essential as a management tool to provide accurate cost information, control waste, and improve the efficiency of healthcare services. This study aims to analyze the role of cost accounting in improving the efficiency of healthcare services using a Systematic Literature Review (SLR) approach. The literature review process was conducted using the PICOS framework to ensure alignment with population, intervention, outcomes, and study design. Articles were retrieved from various national and international scientific databases within a publication period of the last five to ten years. Articles that met the inclusion criteria were qualitatively analyzed to identify how cost accounting is implemented and its impact on efficiency and performance of healthcare services. The results show that the application of cost accounting methods such as responsibility accounting, activity-based costing, and the development of technology-based cost accounting systems makes a positive contribution to improving healthcare service efficiency by increasing the accuracy of cost identification, controlling operational expenditures, and maximizing resource utilization. In addition, the use of digital technology in cost accounting systems enhances transparency, accountability, and the quality of financial information that supports managerial decision-making. Based on these findings, it can be concluded that cost accounting plays an important role in supporting healthcare service efficiency, where the application of appropriate methods, supported by managerial capability and information technology, is a key factor in achieving efficient, sustainable, and high-quality healthcare services.